The validity of heart failure diagnoses in the Finnish Hospital Discharge Register - Matti A. Vuori; Jari A. Laukkanen; Arto Pietilä; Aki S. Havulinna; Mika Kähönen; Veikko Salomaa; Teemu J. Niiranen; FinnGen investigators (SAGE Publications Ltd, 2025)
Background: Contemporary validation studies of register-based heart failure diagnoses based on current guidelines and complete clinical data are lacking in Finland and internationally. Our objective was to assess the positive and negative predictive values of heart failure diagnoses in a nationwide hospital discharge register.
Methods: Using Finnish Hospital Discharge Register data from 2013–2015, we obtained the medical records for 120 patients with a register-based diagnosis for heart failure (cases) and for 120 patients with a predisposing condition for heart failure, but without a heart failure diagnosis (controls). The medical records of all patients were assessed by a physician who categorized each individual as having heart failure (with reduced or preserved ejection fraction) or no heart failure, based on the definition of current European Society of Cardiology heart failure guidelines. Unclear cases were assessed by a panel of three physicians. This classification was considered as the clinical gold standard, against which the registers were assessed.
Results: Register-based heart failure diagnoses had a positive predictive value of 0.85 (95% CI 0.77–0.91) and a negative predictive value of 0.83 (95% CI 0.75–0.90). The positive predictive value decreased when we classified patients with transient heart failure (duration <6 months), dialysis/lung disease or heart failure with preserved ejection fraction as not having heart failure.
Conclusions: Heart failure diagnoses of the Finnish Hospital Discharge Register have good positive predictive value and negative predictive value, even when patients with pre-existing heart conditions are used as healthy controls. Our results suggest that heart failure diagnoses based on register data can be reliably used for research purposes.